Pengaruh Intellectual Capital Disclosure, Firm Size, dan Financial Leverage terhadap Tingkat Underpricing Saham - Isnaini, Fitria Rima; Oktavianna, Rakhmawati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of intellectual capital disclosure, firm size, and financial leverage on stock underpricing in cyclical consumer and non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The sample was collected using the purposive sampling method with several predetermined criteria, resulting in a research sample of 94 companies with a total of 122 data observations. This research obtained using the SPSS version 29 program shows that simultaneously the intellectual capital disclosure, firm size, and financial leverage variables have a significant effect on stock underpricing. Partially, intellectual capital disclosure and firm size affect the level of stock underpricing, while financial leverage do not affect the level of stock underpricing.